Phenolic content, antioxidative properties, and cardio-protective effect of defatted dabai extract - Khoo, Hock Eng (2014)
Dabai (Canarium odontophyllum Miq) is a potential “functional fruit”. This study was aimed to determine phenolics contents, antioxidant capacities, and cardio-protective effects of defatted dabai peel extract. Defatted dabai pulp and pericarp was used for comparison. This study was divided into five parts: (1) Influence of different extraction solvents on phenolic contents and antioxidant capacity of defatted dabai parts (pulp,peel, and pericarp); (2) Optimisation of phenolic extraction in defatted dabai parts using response surface methodology (RSM) and sonication-assisted extraction; (3) Evaluation of antioxidative properties of defatted dabai pulp and peel extracts prepared by solid phase extraction (SPE); (4) Determination of antioxidative and cardio-protective properties of anthocyanins from defatted dabai peel extracts; and (5) Determination of protective effects of anthocyanin-rich defatted dabai peel extracts in hypercholesterolemic rabbits based on histopathological methods (in vivo study). The optimised phenolic-rich crude extract of defatted dabai peel was obtained from the first and second parts of this study while anthocyanin-rich crude extract of defatted dabai peel was obtained after SPE fractionation and LCMS identification of potential phenolic compounds. The results showed that defatted dabai peel extract had the highest total phenolics and antioxidant capacity compared to the pulp extract. The total phenolic content and total anthocyanin content in the methanolic extract defatted dabai peel were 847.8 mg gallic acid equivalent (GAE)/mg extract and 0.018 μg cyanidin-3-glucoside equivalent/mg extract, respectively; while antioxidant capacity of the peel extract had 1034.8 mM TE/mg extract. Ultra high performance liquid chromatography (UHPLC) and liquid chromatography mass spectroscopy (LCMS) analyses confirmed that the defatted dabai peel extract is rich in anthocyanins (~70% of total phenolics), where cyanidin-3-glucoside (55.1 mg/g extract) was the major anthocyanin identified. In vitro chemical and biological assays showed that the anthocyanin-rich extract of defatted dabai peel was a strong antioxidant and had shown potent inhibitory effect against oxidative stress. The anthocyanin-rich extract had 60.1% of scavenging capacity and 1.75 mM TE/g extract as assessed by DPPH and CUPRAC assays, respectively. The defatted dabai peel extract also had high inhibition activities (>60%) based on inhibition of CD36 and PARP-1 ELISA. The results from biological assays also demonstrated that the anthocyanin-rich extract had significantly lower TBARS values as compared to positive control. For in vivo study, three doses of defatted dabai peel extract (1000,2000, and 3000 mg per day) obtained from RSM optimisation and sonication-assisted extraction were supplemented to hypercholesterolemic rabbits for eight weeks. The results revealed that the defatted dabai peel extract is a potential cardio-protective agent,where high dose supplementation reduced severity of hepatic fibrosis, decreased severity of steatosis in kidney, and lessened the degrees of inflammation or atherosclerotic plaques formation in the aorta and right ventricle of the heart of the hypercholesterolemic rabbits. Therefore, defatted dabai peel is a potential source of nutraceutical ingredient for cardio-protection.